2008
DOI: 10.1056/nejmoa0708028
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Carotid Stenting versus Endarterectomy in High-Risk Patients

Abstract: In our trial of patients with severe carotid artery stenosis and increased surgical risk, no significant difference could be shown in long-term outcomes between patients who underwent carotid artery stenting with an emboli-protection device and those who underwent endarterectomy. (ClinicalTrials.gov number, NCT00231270 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
459
0
25

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 740 publications
(503 citation statements)
references
References 16 publications
10
459
0
25
Order By: Relevance
“…This study showed that the survival rate at 5 years was 73%, which is similar to the long‐term results observed in the SAPPHIRE trial (Gurm et al, 2008) and in CEA in patients ≥75 years old (Alozairi et al., 2003). …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study showed that the survival rate at 5 years was 73%, which is similar to the long‐term results observed in the SAPPHIRE trial (Gurm et al, 2008) and in CEA in patients ≥75 years old (Alozairi et al., 2003). …”
Section: Discussionsupporting
confidence: 87%
“…This study shows that 90% of our patients survived up to 3 years and 73% to 5 years. The average mortality rate was similar to the long‐term results reported in the SAPPHIRE trial (Gurm et al., 2008). It suggests that CAS is a reasonable option for most elderly patients because of the high percentage of 3‐year and 5‐year survival rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial was stopped prematurely because of slow enrollment, and many potential participants were excluded because they were considered to be at exceedingly high risk for complications if randomized to undergo CEA. 50 The primary endpoint (the composite of MI, stroke, or death within 30 days plus death because of neurological causes or ipsilateral stroke between 31 days and 1 year) occurred in 12.2% of patients assigned to CAS and 20.1% of those assigned to CEA (p50.004 for noninferiority and p50.053 for superiority). In patients with symptomatic stenosis, the occurrence of the primary endpoint was similar after CAS and CEA (16.8% versus 16.5%,…”
Section: Comparative Assessment Of Carotid Endarterectomy and Stentingmentioning
confidence: 99%
“…Since patients had unrestricted access to carotid endarterectomy (CEA), a proven surgical option with low expected morbidity and mortality, initial investigations in CAS were undertaken in patients with comorbid conditions and/or anatomical features that increased the risk of adverse events (AEs) during CEA. In the past decade, the US Food and Drug Administration (FDA) approved all stent systems studied for an indication of CAS revascularization in these high-surgical-risk patients, based on both randomized controlled and singlearm clinical investigational device exemption (IDE) trials conducted during that period [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%